Pengolahan sampah plastik menjadi vas bunga ecobrick dalam menanggulangi pelonjakan jumlah sampah di daerah sekitar pasar gadang - Rahmalia, Alifa Rahmalia (Maliki Interdisciplinary Journal, 2025)
The amount of plastic waste that continues to increase significantly from year to year has become a very important problem and must be handled with the right steps. Plastic waste belongs to a group of waste that is difficult to decompose, resulting in adverse effects on the ecosystem in the surrounding environment, such as water, soil and humans themselves. Therefore, an innovation is needed to deal with these problems, one of which is by recycling plastic waste into ecobrick flower vases. Ecobricks are a form of recycling that is very easy to implement. Processing plastic waste into ecobricks is not only environmentally friendly but also has use value and even economic value. An ecorick is a bottle filled with pieces of plastic waste and then assembled into the desired shape. Therefore, this article aims to discuss the processing of waste into ecobrick flower vases, to reduce the volume of plastic waste and turn it into one of the products that can be used as an alternative sustainable solution.